Construction of a theoretical model of oscillations of a tillage (seeding) implement with independent mounting and two support rollers - Padalka, Viacheslav; Gorbenko, Oleksandr; Khvostenko, Dmytro; Lazorenko, Andrii; Alpidovskyi, Vladyslav (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates natural harmonic vibrations of a working implement equipped with a lever-type hitching system to the traction mechanisms and two support points on the surface. The task addressed relates to the absence of a generalized theoretical model for quantitative prediction of amplitude-frequency characteristics of such systems. This complicates the substantiation of rational structural and geometric parameters to enable technologically acceptable vertical deviations of working bodies under field irregularities and variable soil properties. A calculation scheme of a two-support lever mechanism has been devised, separating the implement’s intrinsic dynamics from the power unit motion and considering roller-soil contact as an excitation source. An energy-based mathematical model using Lagrange equations of the second kind has been constructed; parametric modeling revealed the decisive influence of attachment geometry and made it possible to determine rational parameter values. The length of the hitch lever to the power unit is 0.5 m, and the distance from the oscillatory system’s center of mass to the hitch point is 0.25 m. The advantage of the results involves the analytical relationship between the mechanism geometry, contact parameters, and vibration characteristics, which enables structural minimization of vertical deviations without mandatory use of active control. The identified regularities are explained by changes in the reduced inertial-elastic characteristics of the system when varying the lever arms and the position of the hitch point relative to the center of mass. The results could be practically applied at the stages of designing and adjusting implements provided that equivalent elastic-damping parameters of the “roller-soil” contact are identified for specific field and soil conditions and operating speeds